PELATIHAN DARING PEMBELAJARAN BERBASIS RISET MENGGUNAKAN MOBILE LEARNING (M-LEARNING) - Noer Saudah; Indah Lestari; Catur Prasastia Lukita Dewi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
The innovative learning model used in Research Based learning requires students to learn actively, independently and not be limited to the space and time that has been scheduled on campus. Searching for data and learning information to support Research Based learning uses the internet network a lot. Besides being able to be more effective and efficient in all respects, the internet network is also very much needed anytime and anywhere by students. In the future, online learning platforms have great potential to be developed not only in times of pandemics like today. And the easiest learning platform for students to use is through mobile learning (m-learning) because it can be ascertained that all young people, in this case students, have phones cell (phones cell). Training activities aim to increase the knowledge and motivation of lecturers in developing learning strategies using Research Based learning in the application of m-learning. So that it can present inspiring and scientific learning